Single-sex education in the 21st century: A 20-year scoping review of the literature. (October 2021) - Robinson, Daniel B.; Mitton, Jennifer; Hadley, Greg; Kettley, Meagan
Abstract: This paper presents a scoping review of literature on single-sex education. There is a long history of single-sex education within most Western primary and secondary educational contexts. The intent is purposefully placed upon the most recent research literature, and an account of single-sex education in the 21st century is mapped out. A total of 70 papers were included in the review, which involved articles from 12 countries and eight school types encompassing elementary and secondary grade levels. The conclusions showcase a need to question claims that suggest providing girls and/or boys with single-sex education, alone, will have a positive influence upon students' academic performance, post-secondary plans, and career readiness. Highlights: This 20-year scoping review presents the most up-to-date research data related single-sex education. The 70 relevant articles attended to the following themes: academic achievement; gender norms; racialized identities; self-concept and self-conceptions; parental/guardian rationale and influence; equity; and labour market/careers. Claims that suggest providing girls and/or boys with single-sex education, alone, will have positive impacts upon students' academic performance ought to be questioned at best and outright dismissed at worst. Though there are some studies that suggest such a causal relationship might be found, they are few and they are not supported by the entire body of literature that exists. Single-sex education does have the potential to enable the challenging or disrupting of some gender norms, by both girls and boys. The body of literature related to single-sex educationdoes present some promising, yet limited, evidence related to creating conditions for equity.